Emotional Resilience in Women: A Quranic Perspective and Literature Review - Siti Aisyah Yusof; Muhammad Saiful Islami Mohd Taher; Farahdina Fazial; Izatul Akmar Ismail; Norhasnira Ibrahim (Global Academic Excellence (GAE), 2025)
Indexed